2021
DOI: 10.1111/nph.17168
|View full text |Cite
|
Sign up to set email alerts
|

Functional traits and symbiotic associations of geoxyles and trees explain the dominance of detarioid legumes in miombo ecosystems

Abstract: Summary The miombo region in Africa is covered by a mosaic of woodlands and geoxylic grasslands and is subject to disturbances such as fires, frost and drought, and low nutrient availability. The dominance of Fabaceae Detarioideae species in miombo ecosystems is remarkable but little understood. We therefore compared plant functional traits (PFTs) of common woody species of the Angolan plateau, grouped by life form (trees, geoxyles), lineage (Fabaceae: Detarioideae, non‐Detarioideae) and symbiont association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…In cases where the relationship between a principle component and biodiversity was significant, we then used the three traits with the highest loading on that component in further correlation analyses. As other studies have shown that trait to function correlations may vary between different functional groups of plants (Gomes et al, 2021 ), we separated tree species in two functionally different groups, dipterocarps and non‐dipterocarps, and performed correlation analyses on each group separately. All of the above analyses were conducted in JMPpro 14.0.0 (SAS, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…In cases where the relationship between a principle component and biodiversity was significant, we then used the three traits with the highest loading on that component in further correlation analyses. As other studies have shown that trait to function correlations may vary between different functional groups of plants (Gomes et al, 2021 ), we separated tree species in two functionally different groups, dipterocarps and non‐dipterocarps, and performed correlation analyses on each group separately. All of the above analyses were conducted in JMPpro 14.0.0 (SAS, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…LMA was calculated as dry leaf biomass divided by total leaf area [4]. We used the same leaves to calculate LT by using a digital caliper at an intermediate position between the leaf margin and the midrib for each leaf [52]. We then used the average value of each plot as LT.…”
Section: Economic Traitsmentioning
confidence: 99%
“…Temperature is the key driving force ofthe formation of soil microbial communities because it affects the carbon utilization, structure, and functions of fungi [89] and plays an essential role in the decomposition and transformation of soil nutrients [90]. The BNF is also affected by temperature, water, and salt conditions [50,52]. Consequently, temperature affects nitrogen concentration in the leaves of A. sparsifolia.…”
Section: Contributions Of Environmental Variables On the Leaf Functional Traits Of A Sparsifoliamentioning
confidence: 99%
“…Understanding how traits and suites of traits evolved and interacted with the historical assembly of species comprising biomes through time can lead to a greater understanding of biome history (Couvreur et al, 2015). Different Ziziphus species have distinct life forms including trees, lianas, and dwarf shrubs with massive underground woody structures and limited aerial parts hereafter referred to as geoxyles (Gomes et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…
Functional traits are a way to infer processes from pattern, and as such are used to disentangle the macroecology and biogeography of plant families (e.g., Onstein et al, 2019;Xue et al, 2020) and biomes (e.g., Gomes et al, 2020;Solofondranohatra et al, 2018), but only infrequently plant genera (although see Proches et al, 2012;Pezzini et al, 2021). As morpho-physio-phenological characters, functional traits relate to the life history strategies of plants that embody growth, reproduction, and survival (Violle et al, 2007) and indicate how species relate to the environment.
…”
mentioning
confidence: 99%